Functional characterization of seven terpene synthases from Ophiopogon japonicus via engineered Escherichia coli - Wen Xu; Qing Ma; Tong Chen; Haiyan Zhang; Guanglei Ma; Sibongile Mafu; Juan Guo; Xiaohui Fan; Guanghong Cui; Baolong Jin (Science of Traditional Chinese Medicine)
Abstract. Background. Ophiopogon japonicus (L.f) Ker-Gawl. growing in Zhejiang is recognized as the Dao-di medicinal herb for the production of Ophiopogonis Radix. Borneol-7-O-[β-D-apiofuranosyl-(1→6)]-β-D-glucopyranoside, a prominent pharmacologically active compound, serves as a marker distinguishing O. japonicus in Zhejiang from those in other geographical areas. It is synthesized from borneol through glycosylation, with terpene synthase (TPS) being the critical enzyme catalyzing the conversion of terpene precursors into borneol. Objective. The aim of the study was to define key genes involved in biosynthesis of borneol in O. japonicus. Methods. The candidate terpene synthase genes were identified from the root and leaf transcriptome data of O. japonicus in Zhejiang and the functions of these enzymes were identified using engineered Escherichia coli. Results. This study developed a rapid expression system for monoterpene and sesquiterpene synthases based on engineered E. coli. Seven terpene synthase genes (OjTPS1 to OjTPS7) were identified in different terpene synthase subfamilies, including 2 from TPS-a, 4 from TPS-b, and 1 from TPS-g. Biochemical analysis using an engineered system E. coli demonstrated that all the 7 terpene synthases produced monoterpenes, and OjTPS3, OjTPS5, and OjTPS6 also yielded sesquiterpenes. Conclusions. These 7 terpene synthases produced 13 monoterpenes and 8 sesquiterpenes. Notably, OjTPS1 produced borneol establishing the groundwork for elucidating the biosynthetic pathways of borneol-7-O-[β-D-apiofuranosyl-(1→6)]-β-D-glucopyranoside and other volatile oil components.